2012
DOI: 10.1007/s10570-011-9643-7
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis of the adsorption of xylans on cellulose surface

Abstract: In order to model the adsorption of xylan on cellulose, we have simulated, at the atomic level, the gas phase adsorption of small xylan fragments having 5 skeletal b (1 ? 4) xylosyl residues (X 5 ), using molecular dynamics simulations. A first regime was considered, corresponding to a low surface coverage, with the adsorption of isolated X 5 in various initial orientations. In this regime, the simulation indicated that X 5 moved toward extended conformations, some of them being helical, with the possibility o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 54 publications
5
36
0
Order By: Relevance
“…In line with our findings, MD simulations of xylan adsorption onto a cellulose surface in gas phase showed that side groups did not affect the ability of one xylan molecule to adsorb onto a surface (Mazeau and Charlier, 2012). In addition to this, our free energy calculations showed that side groups, and especially the XXXU m U m X structure, where mGlcA are pointing toward the cellulose surface, had a positive impact on the interaction between xylan and cellulose.…”
Section: Discussionsupporting
confidence: 89%
“…In line with our findings, MD simulations of xylan adsorption onto a cellulose surface in gas phase showed that side groups did not affect the ability of one xylan molecule to adsorb onto a surface (Mazeau and Charlier, 2012). In addition to this, our free energy calculations showed that side groups, and especially the XXXU m U m X structure, where mGlcA are pointing toward the cellulose surface, had a positive impact on the interaction between xylan and cellulose.…”
Section: Discussionsupporting
confidence: 89%
“…Such lowering of the interaction strength between the substrate and the surface induced by the explicit presence of water molecules have been recently documented and discussed in the case of the interaction between xylan and cellulose (Mazeau and Charlier 2012).…”
Section: Adsorption Process In Aqueous Environmentmentioning
confidence: 94%
“…Xylan backbones are very similar in structure to cellulose, with both macromolecules built of glycopyranose rings in the 4 C 1 chair conformation linked to one another by b-1,4 diequatorial glycosidic bonds. This means that the gross features of their potential energy surfaces are very similar (Mazeau and Charlier, 2012). As such, there is a high affinity between the two species, and xylan adsorbs irreversibly onto cellulose surfaces (Kabel et al, 2007;Köhnke et al, 2011).…”
Section: Xyl Contents In Outer Soluble Mucilage Show Tight Proportionmentioning
confidence: 99%